Tutorials in motor behavior - Stelmach, George E.; Requin, Jean (Advances in psychology (Amsterdam, Netherlands), 1980)
The contributors to this book are all distinguished, internationally-known specialists working in the motor control and learning area. The result is a unique collection of papers that discuss many aspects of this intricate and diverse subject and at the same time manage to provide the reader with a good overview of the major topics.